2021
DOI: 10.1088/1757-899x/1029/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Improving the lubricating properties of transmission oils by activating the processes of boundary films formation

Abstract: The properties of the boundary lubricating films determine the performance of friction units, which is most important in the event of a loss of lubricant. It has been found that when sunflower oil is added to mineral transmission oil, strong boundary layers are formed during friction. These layers reduce wear and friction. Vegetable oils with the lowest iodine value have the best antiwear properties. The additional introduction of the product of the interaction of rosin with copper (II) hydroxide into the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Bahari et al (2018) showed that the presence of vegetable oils improves and dominates the tribological properties of minerale/vegetable oil blends [15]. In 2021, Ponomarenko et al found that when sunflower oil is added to mineral transmission oil, strong boundary layers are formed during friction reducing wear and friction [12]. At ambient temperature, Reeves et al (2015) demonstrated that natural oils with high oleic acid concentration present better friction performances [30].…”
Section: Influence Of the Presence Of Vo As Bio-additivementioning
confidence: 99%
See 1 more Smart Citation
“…Bahari et al (2018) showed that the presence of vegetable oils improves and dominates the tribological properties of minerale/vegetable oil blends [15]. In 2021, Ponomarenko et al found that when sunflower oil is added to mineral transmission oil, strong boundary layers are formed during friction reducing wear and friction [12]. At ambient temperature, Reeves et al (2015) demonstrated that natural oils with high oleic acid concentration present better friction performances [30].…”
Section: Influence Of the Presence Of Vo As Bio-additivementioning
confidence: 99%
“…Due to their adhesion to metallic surfaces, the long chain of polar fatty acids constituting the structure of the triacylglycerol is responsible for the interest of using natural oils in boundary lubrication by creating a protective thin monolayer, which allows us to reduce friction and wear of the sliding surfaces [10]. Numerous studies have been focused on vegetable oils as surfactant molecules added to engine oils to reduce friction in the boundary lubrication regime [11][12][13][14]. In 2018, Bahari et al experimented with the tribological response of vegetable oils (palm oil, soybean oil) and their blends with mineral engine oil in a reciprocating sliding contact running in severe conditions [15].…”
Section: Introductionmentioning
confidence: 99%